(untitled) (Baghdad Science Journal, 2018)
A comparative investigation of gas sensing properties of SnO2 doped with WO3 based on thin film and bulk forms was achieved. Thin films were deposited by thermal evaporation technique on glass substrates. Bulk sensors in the shape of pellets were prepared by pressing SnO2:WO3 powder. The polycrystalline nature of the obtained films with tetragonal structure was confirmed by X-ray diffraction. The calculated crystalline size was 52.43 nm. Thickness of the prepared films was found 134 nm. The optical characteristics of the thin films were studied by using UV-VIS Spectrophotometer in the wavelength range 200 nm to 1100 nm, the energy band gap, extinction coefficient and refractive index of the thin film were 2.5 eV , 0.024 and 2.51, respectively. Hall measurements confirmed that the films are n-type. The NO2 sensing characteristics of the SnO2:WO3 sensors were studied with various temperatures and NO2 gas concentrations. Both thin film and bulk sensors showed maximum sensitivity at temperature of 250 oC. Thin film sensors showed enhanced response in comparison to that of pellets.